Group 2 Innate Lymphoid Cells in Pulmonary Immunity and Tissue Homeostasis - Mindt, Barbara C.; Fritz, Jörg H.; Duerr, Claudia U. (Frontiers in Immunology, 2018)
Group 2 innate lymphoid cells (ILC2) represent the most recently identified member of the family of innate lymphoid cells and have received much attention since their detailed description in 2010. They can orchestrate innate as well as adaptive immune responses as they interact with and influence several immune and non-immune cell populations. Moreover, ILC2 are able to rapidly secrete large amounts of type 2 cytokines that can contribute to protective but also detrimental host immune responses depending on timing, location and physiological context. Interestingly, ILC2, despite their scarcity, are the dominant innate immune cell population in the lung, indicating a key role as first responders and amplifiers upon immune challenge at this site. In addition, the recently described tissue residency of ILC2 further underlines the importance of their respective microenvironment. In this review we provide an overview of lung physiology including a description of the most prominent pulmonary resident cells together with a review of known and possible ILC2 interactions within this unique environment. We will further outline recent observations of pulmonary ILC2 during immune challenge including respiratory infections and discuss different models and approaches to study ILC2 biology in the lung.